Modal Sodial dalam Pemberdayaan Desa Pakraman : Studi Kasus Pengelolaan LPD Des Pakraman Batuaji Kawan, Kabupaten Tabanan, Propinsi Bali - I Made Kristiadi Putra; Indri Apriliyanti (Magister Administrasi Publik, 2010)
The existence of social capital is really important in development because social capital plays a role to achieve sustainability development. It also applies in community development process. Community development strategy can be implemented through empowering the institution and civil society organizations. Those are form of social capital that develops in society. Bali province government has been adapting the existence of social capital through the empowerment of Pakraman village. Pakraman Village is an indigenous community that is formed on the socio-religious bound. The most common way to empower society is based on the establishment of village credit institutions (Lembaga Pengkreditan Desa: LPD) One of the LPD that shows its existence in the midst of intense competition with other financial institution is LPD Pakraman Batuaji Kawan Village in Tabanan, Bali Province. Thus, this paper is aimed to elaborate the contribution of social capital in management of LPD Pakraman Batuaji Kawan Village. The research methodology that had been used in this paper was qualitative descriptive with case study approach. Meanwhile, data collection techniques that had been used in this research were interview, observation and documentation. The result of this research show that social capital has a positive role in supporting the management of LPD such as the planning and budgeting activities, personnel recruitment process, the lending process, the process of resolving non performing loans, the process of supervision and accountability. Based on these result, the adoption of social capital in the process of community empowerment plays significance role in maintaining the community empowerment's program.